Incomplete femoral neck fracture with characteristics of atypical femoral fracture: A case report and literature review - Yasuhiro Higai; Yuji Kanaya; Hiroyoshi Hagiwara; Yuichirou Yano; Takashi Fukushima; Norihiro Akazawa; Takahiro Shimizu; Sueo Nakama; Katsushi Takeshita (Trauma Case Reports)
Femoral neck fractures are considered exclusion criteria for atypical femoral fractures; however, femoral neck fractures with atypical femoral fractures have also been reported. Here, we report a case of a femoral neck fracture with features of atypical femoral fractures and a review of the related literature. A 76-year-old woman had been treated with denosumab for five years. The patient had no history of trauma, but complained of pain in the right hip. Radiological examination revealed an incomplete fracture of the right femoral neck. Internal fixation was performed, but fusion was delayed. Bipolar hemiarthroplasty was performed four months after surgery. In a patient with long-term bisphosphonate use, complaints of hip pain could indicate the possibility of an atypical fracture. According to the existing literature, as with atypical femoral fractures, this fracture has a high risk of delayed union; therefore, temporary prosthetic replacement should be considered as a treatment option.